UPAYA KOREA SELATAN DALAM MENJADIKAN KIMCI SEBAGAI WARISAN BUDAYA DUNIA - Herdian, Praja; Waluyo, Tri Joko (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Kimchi is a traditional Korean food. Kimchi existed before the breakup of Korea into two parts into South Korea and North Korea. South Korea in the modern era was diligent in registering its culture, as well as Kimchi. Kimchi has been a part of South Korean people's lives for generations, so the process of making Kimchi which has the name Kimjang has been recognized by UNESCO as a Culture of No Human Heritage. In the modern world, culture has become one of the strengths of a country, in addition to economic and military power, as expressed by Milton Chumming in his theory of cultural diplomacy. This has resulted in South Korea benefiting from the spread of Korean culture, named Haliyu Wave. South Korea can increase the ability of its soft power by trying to register Kimchi on an international body that is credible and has been recognized internationally, namely UNESCO. South Korea considers Kimchi as a valuable asset because of its popularity in foreign countries. It is unfortunate if the ownership falls in the hands of its rivals, namely North Korea, which is the only country that has a policy to increase Kimchi production in its country. This factor triggered South Korea to register Kimchi on international bodies. When South Korea reaches its goals, its soft power will increase, so that the position of the South Korean economy will increase.   Keywords: Kimchi traditional food of Korea, Kimchi UNESCO, Kimchi South                                                                                                                                                                                and North Korea.